IMPLEMENTATION OF TRADITIONAL-BASED NUMERACY LITERACY LEARNING MEDIA IN BANTIMOH PAUD, WEU LHOK VILLAGE, MONTASIK DISTRICT, ACEH BESAR REGENCY - Anzora, Anzora; Aryani, Irma; Ridha, Usfur; dauyah, Ema; Erliana, Nova (Universitas Muhammadiyah Aceh, 2025)
Bantimoh Early Childhood Education (PAUD) is a preschool located in Weu Lhok Village, Montasik District, Aceh Besar, located in the mountains, where the population is predominantly farmers and gardeners. A survey and interviews with the principal revealed a lack of numeracy literacy learning media at the PAUD. This Community Service (PKM) aims to implement learning media based on the traditional game of snakes and ladders as a means of improving literacy and numeracy for early childhood children at Bantimoh PAUD. The PKM implementation method includes media design, outreach to teachers and parents, game implementation assistance, and evaluation of child development. The results of the activity indicate an increase in learning interest, understanding of number concepts, letter recognition, and simple arithmetic skills in children. In addition, teachers obtained alternative creative learning media that can be applied in daily teaching and learning activities. Thus, the implementation of the snakes and ladders numeracy literacy media at Bantimoh PAUD is effective in supporting the achievement of basic competencies for early childhood.